2021
DOI: 10.1136/bmj.n532
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of interventions for reducing symptoms of depression in people with dementia: systematic review and network meta-analysis

Abstract: Objective To describe the comparative efficacy of drug and non-drug interventions for reducing symptoms of depression in people with dementia who experience depression as a neuropsychiatric symptom of dementia or have a diagnosis of a major depressive disorder. Design Systematic review and meta-analysis. Data sources Medline, Embase, the Cochrane Library, CINAHL, PsycINFO, and grey literature between incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 112 publications
1
66
0
1
Order By: Relevance
“…The most important thing for us, as therapists, to do for (very) older patients with so-called psychogenic symptoms is to accept their symptoms in a supportive manner while conducting tests in small doses, minimizing the use of medications, and looking for ways to distract them from their symptoms in their daily lives. A recent systematic review also reported that nonpharmacological interventions are more effective than pharmacological interventions in reducing symptoms of depression in dementia patients without MDD [ 121 ]. The best thing to do is to encourage these older adults to immerse themselves in whatever interests them, and if they have outstanding abilities, it is best to help them exercise those abilities.…”
Section: Burden Of and Responses To Aging And Dementiamentioning
confidence: 99%
“…The most important thing for us, as therapists, to do for (very) older patients with so-called psychogenic symptoms is to accept their symptoms in a supportive manner while conducting tests in small doses, minimizing the use of medications, and looking for ways to distract them from their symptoms in their daily lives. A recent systematic review also reported that nonpharmacological interventions are more effective than pharmacological interventions in reducing symptoms of depression in dementia patients without MDD [ 121 ]. The best thing to do is to encourage these older adults to immerse themselves in whatever interests them, and if they have outstanding abilities, it is best to help them exercise those abilities.…”
Section: Burden Of and Responses To Aging And Dementiamentioning
confidence: 99%
“…Multidisciplinary care and interventions such as massage and touch therapy lead to clinically meaningful reductions in symptoms (ie, the threshold above which clinicians, patients, and researchers perceive a change on an outcome scale) of agitation and aggression, as per a systematic review (189 studies, 25 736 patients, 17.5% of studies conducted in a clinic/community setting) published in 2019 11. Another systematic review published in 2021 (256 studies, 28 483 patients, 41% of studies conducted in a clinic/community setting) found that multidisciplinary care, occupational therapy, and non-medication interventions (eg, animal therapy and exercise, fig 2) resulted in clinically meaningful reductions in symptoms of depression in people with dementia (without a major depressive disorder) 12. Medications alone were not more efficacious than usual care in both of these reviews 68.…”
Section: How To Manage Neuropsychiatric Symptoms In People With Dementiamentioning
confidence: 99%
“…Missing outcome data and a lack of participant blinding limit validity of findings (table 4). 1112 Studies included in these systematic reviews ranged from less than one week to two years in duration and were conducted across different care settings (eg, community, nursing home) in predominantly high income countries 1112. The comparative cost effectiveness of efficacious interventions identified in these systematic reviews is unknown.…”
Section: How To Manage Neuropsychiatric Symptoms In People With Dementiamentioning
confidence: 99%
“…They also assessed study quality with the Cochrane Risk of Bias 2.0 tool. 19 We used a hierarchy developed by an expert psy chiatrist a priori to select an outcome from each study for inclusion in metaanalysis 20 when the same mental health outcome was measured with more than 1 validated tool, whereby we prioritized observerrated tools above selfrated tools, commonly used tools over less commonly used tools, and tools measuring specific symptoms over those measuring mixed symptoms.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%